Darcy-Forchheimer flow of second-grade fluid in a porous medium using Cattaneo-Christov model - Khan, Nargis; Saeed, Mobashar; Hashmi, M. S.; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2023)
This research paper examines the Darcy-Forchheimer flow of second-grade hybrid nanofluid with thermophoretic particle deposition on a solar collector plate in a porous media. This study performs an extensive exploration of entropy generation. Solar collector plates play a crucial role in energy storage in solar power plants. They help to store and regulate energy at extreme temperatures. This work analyzes the performance of a solar collector plate when the conventional fluid of Ethylene Glycol (EG) is reciprocated by nanoparticles of zirconium dioxide and copper. The ramifications of Magntohydrodynamic (MHD) and Cattaneo-Christov heat and mass flux are also investigated. The expressions of mass and energy are generated by using the Cattaneo-Christov model of heat and mass flux. The Homotopy analysis method (HAM) is utilized to achieve the results of differential equations against various dimensionless parameters. The fluctuating behavior of velocity, concentration and temperature profiles is discussed graphically in this paper. Furthermore, tables are included for the numerical values of skin friction, Sherwood number and Nusselt number for several parameters. As the value of the Darcy parameter raises, the fluid's velocity distribution continuously reduces. The temperature distribution reduces along with the greater values of the thermal relaxation parameter. The concentration profile has shown decreasing impact due to the increasing value of the concentration relaxation parameter.
Keywords: Darcy-Forchheimer flow; second-grade hybrid nanofluid; Cattaneo-Christov model; thermophoretic particle deposition